NEMATÃ“IDES DO GÃŠNERO ð˜”ð˜Œð˜“ð˜–ð˜ð˜‹ð˜–ð˜Žð˜ ð˜•ð˜Œ EM PROJETO INTERNACIONAL - Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
NEMATÃ“IDES DO GÃŠNERO ð˜”ð˜Œð˜“ð˜–ð˜ð˜‹ð˜–ð˜Žð˜ ð˜•ð˜Œ EM PROJETO INTERNACIONAL